MENGGUNAKAN TEKNOLOGI BLOCKCHAIN UNTUK MEMASTIKAN KEAMANAN - R.V, Nesterenko (CV. Hawari, 2022)
The use of Blockchain in the Internet of Things networks is an innovative approach that can make communication between devices of such a network distributed, autonomous and secure. The blockchain in this context is a set of cryptographically connected blocks. Transactions in the network act as the main carriers of information about the state of the nodes, as well as the output information of the nodes themselves for the autonomous functioning of the network. A node is a